Application of endovascular embolization of the middle meningeal artery in the treatment of chronic subdural hematomas: A literature review - Kotlyarevskyi, Yurii O.; Serhiienko, Yuliia G.; Piatykop, Volodymyr O. (Ukrainian neurosurgical journal, 2025)
Introduction. Interest in this research topic arises from the fact that chronic subdural hematoma (CSDH) is currently one of the most common neurosurgical diagnoses in adults. Over the past decade, the incidence of CSDH has more than doubled. Recent studies have significantly enhanced our understanding of the mechanisms underlying the formation of CSDH, linking it to recurrent microbleeds in the subdural space from fragile, newly formed vessels within the hematoma capsule. Most of these vessels originate from the distal branches of the middle meningeal artery (MMA). Accordingly, endovascular embolization of the MMA may help eliminate chronic recurrent bleeding into the subdural space and facilitate hematoma resorption. Objective of the study. To summarize current concepts regarding the pathophysiology of CSDHs and analyze the implementation and use of endovascular embolization of the MMA in contemporary treatment strategies for CSDH based on literature data. Results. A detailed analysis of the literature indicates that a new understanding of the primary pathological process of CSDH has substantiated approaches to diagnosing and treating this pathology as an angiogenic process. Recent research findings demonstrate that endovascular embolization of the MMA in patients with CSDH is a safe and effective method to prevent recurrence or progression of subdural hematomas. Comparing different classes of embolic materials in the treatment of patients with CSDH represents the next step in ongoing research aimed at standardizing the overall treatment protocol for chronic subdural hematoma. Интерес к выбранной теме исследования вызван тем, что хроническая субдуральная гематома является одним из наиболее распространенных нейрохирургических диагнозов у взрослых. В последнее десятилетие наблюдается тенденция к возрастанию заболеваемости хроническими субдуральными гематомами более чем в два раза. На основании данных исследований, проведенных недавно, значительно расширено представление о механизме формирования хронических субдуральных гематом. Его связывают с рецидивирующими микрокровоизлияниями в субдуральное пространство из хрупких недавно образованных сосудов капсулы гематомы. Большинство этих сосудов происходят из дистальных ветвей средней оболочечной артерии. Поэтому эндоваскулярная эмболизация средней оболочечной артерии может способствовать устранению хронического повторного кровотечения в субдуральное пространство и процессу резорбции гематомы. Обобщены современные представления о патофизиологии хронических субдуральных гематом. Рассмотрены внедрение и использование эндоваскулярной эмболизации средней оболочечной артерии в современных стратегиях лечения хронических субдуральных гематом по данным литературных источников. Новое понимание первичного патологического процесса хронических субдуральных гематом позволило обосновать подходы к диагностике и лечению этой патологии как ангиогенного процесса. Результаты исследований, проведенных в последние годы, свидетельсвуют о том, что эндоваскулярная эмболизация средней оболочечной артерии у пациентов с хроническими субдуральными гематомами является безопасным и эффективным методом для предотвращения рецидива/прогрессирования субдуральной гематомы. Сравнение использования разных классов эмболизирующих материалов в лечении пациентов с хроническими субдуральными гематомами является следующим этапом в продолжающихся исследованиях для стандартизации общей схемы лечения хронических субдуральных гематом. Інтерес до обраної теми дослідження спричинений тим, що хронічна субдуральна гематома є одним із найпоширеніших нейрохірургічних діагнозів у дорослих. В останнє десятиріччя спостерігається тенденція до зростання захворюваності на хронічні субдуральні гематоми більш ніж удвічі. На підставі даних досліджень, проведених недавно, значно розширено уявлення про механізм формування хронічних субдуральних гематом. Його пов’язують із рецидивними мікрокрововиливами в субдуральний простір із крихких новоутворених судин капсули гематоми. Більшість цих судини походять із дистальних гілок середньої оболонкової артерії. Тому ендоваскулярна емболізація середньої оболонкової артерії може сприяти усуненню хронічної повторювальної кровотечі в субдуральний простір і процесу резорбції гематоми. Узагальнено сучасні уявлення щодо патофізіології хронічних субдуральних гематом. Розглянуто впровадження та використання ендоваскулярної емболізації середньої оболонкової артерії в сучасних стратегіях лікування хронічних субдуральних гематом за даними літературних джерел. Нове розуміння первинного патологічного процесу хронічних субдуральних гематом дало змогу обґрунтувати підходи до діагностики та лікування цієї патології як ангіогенного процесу. Результати досліджень, проведених останніми роками, свідчать про те, що ендоваскулярна емболізація середньої оболонкової артерії в пацієнтів із хронічними субдуральними гематомами є безпечним і ефективним методом для запобігання рецидиву/прогресуванню субдуральної гематоми. Порівняння використання різних класів матеріалів, що емболізують, у лікуванні пацієнтів із хронічними субдуральними гематомами є наступним етапом в дослідженнях, що тривають, для стандартизації загальної схеми лікування хронічних субдуральних гематом.